“Lenin in Swaddling Clothes”: A Critique of the Ideological Conflict Between Socialist State Policy and Christian Music in Cold War Romania - Pieslak, Sabina Pauta (Current Musicology, 2004)
On April 11 , 1924, the monarchic government of Romania decreed, through the so-called “Gheorghe Marzescu” law, that the political practice of Communism was subversive to the national cause and therefore illegal. Until the ban was lifted in 1944, the government imprisoned members of the Romanian Communist Party (Constantiniu 2002:309). To raise funds for their incarcerated comrades while avoiding official detection, groups of activists belonging to Red Assistance International (Ajutorul Rosu International) adapted certain winter caroling practices of the Christian Orthodox Church. Instead of singing star songs (cemtece de stea) or Christmas carols (colinde) and carrying staffs bearing the star of Bethlehem with the image of the infant Jesus in swaddling clothes, the activists sang altered texts that urged listeners to contribute money to the cause of the working class and carried staffs decorated with a five-pointed star emblazoned with Lenin’s image (Cernea, Radulescu, and Pintean 1964:124-25).